Alcohol intake and binge drinking among Italian adolescents: The role of drinking motives. Issue 2 (2nd April 2016) - Laghi, Fiorenzo; Baumgartner, Emma; Baiocco, Roberto; Kotzalidis, Georgios D.; Piacentino, Daria; Girardi, Paolo; Angeletti, Gloria
ABSTRACT: Binge drinking, a pattern associated with worse outcome, is becoming increasingly popular among youths, thus negatively impacting social life. To investigate drinking patterns and their underlying motives in Italian adolescents, the Alcohol Use Questionnaire and the Drinking Motive Questionnaire Revised Short Form were administered to 332 school-age teenagers (16–19 years; 139 girls, 193 boys) from a single Roman school, recruited at their classrooms through the intermediation of their teachers. Boys scored higher than girls on all drinking and binge measures. They also scored higher on the Enhancement, Social, and Conformity Drinking Motive Questionnaire–Revised Short Form subscales. Binge drinking scores positively correlated with gender, alcohol consumption, and with all Drinking Motive Questionnaire Revised Short Form subscales. In the two-step hierarchical model, Drinking Motive Questionnaire–Revised Short Form enhancement and conformity predicted alcohol use and Drinking Motive Questionnaire–Revised Short Form coping motives significantly predicted binge drinking. Binge drinking is prevalent among Italian adolescents, who mainly drink to enhance perceived positive effects of alcohol, conform to their social groups, and face their problems. Boys binge more than girls.